Examining the impact of the first wave of COVID-19 and associated control measures on interventions to prevent blood-borne viruses among people who inject drugs in Scotland: an interrupted time series study. (1st March 2022) - Trayner, Kirsten M.A.; McAuley, Andrew; Palmateer, Norah E.; Yeung, Alan; Goldberg, David J.; Glancy, Megan; Hunter, Carole; Ritchie, Trina; Craik, Julie; Raeburn, Fiona; McTaggart, Stuart; Barnsdale, Lee; et al.
Abstract: Background: COVID-19 has likely affected the delivery of interventions to prevent blood-borne viruses (BBVs) among people who inject drugs (PWID). We examined the impact of the first wave of COVID-19 in Scotland on: 1) needle and syringe provision (NSP), 2) opioid agonist therapy (OAT) and 3) BBV testing. Methods: An interrupted time series study design; 23rd March 2020 (date of the first 'lockdown') was chosen as the key date. Results: The number of HIV tests and HCV tests in drug services/prisons, and the number of needles/syringes (N/S) distributed decreased by 94% (RR=0.062, 95% CI 0.041–0.094, p < 0.001), 95% (RR=0.049, 95% CI 0.034–0.069, p < 0.001) and 18% (RR = 0.816, 95% CI 0.750–0.887, p < 0.001), respectively, immediately after lockdown. Post-lockdown, an increasing trend was observed relating to the number of N/S distributed (0.6%; RR = 1.006, 95% CI 1.001–1.012, p = 0.015), HIV tests (12.1%; RR = 1.121, 95% CI 1.092–1.152, p < 0.001) and HCV tests (13.2%; RR = 1.132, 95 CI 1.106–1.158, p < 0.001). Trends relating to the total amount of methadone prescribed remained stable, but a decreasing trend in the number of prescriptions (2.4%; RR = 0.976, 95% CI 0.959–0.993, p = 0.006) and an increasing trend in the quantity prescribed per prescription (2.8%; RR = 1.028, 95% CI 1.013–1.042, p < 0.001) was observed post-lockdown. Conclusions: COVID-19 impacted the delivery of BBV prevention services for PWID in Scotland. While there is evidence of service recovery; further effort is likely required to return some intervention coverage to pre-pandemic levels in the context of subsequent waves of COVID-19. Highlights: Study assessing the impact of COVID-19 on BBV prevention services for PWID. Used data from service administration systems across a range of BBV prevention services. Some service delivery was severely affected, most notably in relation to BBV testing. Conversely, overall trends in drug treatment prescribing remained stable. Evidence of recovery but some service provision had not returned to pre-pandemic levels.